Development of a Model for Enhancing Justice in MPA Designation and Zoning and its Application to Taiwan's South Penghu Marine National Park. Issue 6 (2nd November 2019) - Chung, Huey-Shian Elly; Gullett, Warwick; Rose, Gregory
Abstract: Multi-purpose marine protected areas (MPAs) are prevalent world-wide as institutional mechanisms deployed in the marine environment to manage multiple uses, conserve resources and protect ecosystems. Yet some people may experience disadvantage following the implementation of new MPAs. One understudied aspect of MPAs is the distribution of advantages and disadvantages and how best to address the "justice" concerns that they raise. This article identifies a framework of principles, methods and tools to address these concerns. It devises a "MPA justice model" and demonstrates its applicability to a Taiwanese case study. In 2014, Taiwan proclaimed its first multiple-purpose MPA, the South Penghu Marine National Park and the case study shows ways that the MPA's socio-economic sustainability could have been better accomplished. The article focuses on future MPA establishment that incorporates distributional fairness and procedural legitimacy into MPA site designation and zoning design - but might also be adapted to use retrospectively in MPA review processes.